PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP NIAT MENGGUNAKAN INTERNET BANKING DENGAN SIKAP SEBAGAI VARIABEL INTERVENING - MEGA LARASATI, IRA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this research is to know the effect of perceived ease of use and perceived usefulness to the intention of using internet bankingBCA with attitude as intervening variable. The population in this research are BCA customers in Darmo Surabaya.This research is a causality research with quantitative approach. Technique of sampling using non probability sampling with amount 220 respondents. Statistical analysis in this study is path analysis with the help of AMOS 22.0 version software. The results of this study explain that a significant perceived ease of use on attitude, perceived usefulness on attiude, perceived ease of use on intention to use, perceived usefulness on intention to use and attitude on intention to use. Keywords: perceived ease of use, perceived usefulness, attitude, intention to use , internet banking